CD44 SNP rs187115: A novel biomarker signature that predicts survival in resectable pancreatic ductal adenocarcinoma. - Stracquadanio, G; Vrugt, B; Flury, R; Schraml, P; Würl, P; Müller, T; Knippschild, U; Henne-Bruns, D; Breitenstein, S; Clavien, P; Graf, R; Bond, G; et al. (American Association for Cancer Research, 2016)
Purpose Although pancreatic ductal adenocarcinoma (PDAC) is an aggressive tumor, like other common cancers, it displays a wide range of biology. However, at present, there are no reliable tests to predict patients’ cancer-specific outcomes and guide personalized treatment decisions. In this study, we aim to identify such biomarkers in resectable PDAC by studying single nucleotide polymorphisms (SNPs) in the CD44 gene, which drives the progression of pancreatic cancer. Experimental Design 348 PDAC patients from three independent cohorts (Switzerland, Germany, The Cancer Genome Atlas (TCGA)) who underwent pancreatic resection are included in the study. Information on the haplotype structure of the CD44 gene is obtained using 1000 Genomes Projectdata and the genotypes of the respective tagging SNPs are determined. Cox proportional hazards models are utilized to analyze the impact of SNP genotype on patients´ survival. Results We identify a SNP in the CD44 gene (SNP rs187115) that independently associates with allelic differences in prognosis in all study cohorts. Specifically, in 121 Swiss patients, we observe an up-to 2.38-fold (p=0.020) difference in tumor-related death between the genotypes of SNP rs187115. We validate those results in both the German (hazard ratio (HR)=2.32, p=0.044, 101 patients) and the TCGA cohort (HR=2.36, p=0.044, 126 patients). Conclusions CD44 SNP rs187115 can serve as a novel biomarker readily available at the time of PDAC diagnosis that identifies patients at risk for faster tumor progression and guide personalized treatment decisions. It has the potential to significantly expand the pool of patients that would benefit from tumor resection